Material Effects on the Electrocapacitive Performance for the Energy-storage Electrode with Nickel Cobalt Oxide Core/shell Nanostructures. (1st October 2017) - Lin, Lu-Ying; Lin, Lu-Yin
Graphical abstract: Highlights: Material intrinsic property effects on the electrocapacitive performance are studied. Core/shell morphology variation is minimized and restricted to a sheet-on-sheet one. NiCo2 O4 core materials with the NiSx, NiOx, NiMox Oy, and MnOx shells are synthesized. The NiCo2 O4 /NiSx electrode got a specific capacitance of 6.12 F cm −2 at 1 mA cm −2 . An asymmetric supercapacitor with the NiCo2 O4 /NiSx and carbon electrodes is made. Abstract: Core/shell nanostructures of metal oxides and sulfides are intensively studied as the energy-storage materials. Most researchers focus on a single core/shell system and optimize the morphology of nanomaterials to enhance the electrochemical performance, but limited reports studying the effect of the material category in the same morphology on the performance of the core/shell electrode. In this work, multiple core/shell systems based on the similar sheets-on-sheets morphology are made using the same NiCo2 O4 core and different shells of NiSx, NiOx, NiMox Oy and MnOx . By minimizing the effects of the morphology for the core/shell structure, the material category is verified to play important roles on the electrochemical performances of the electrodes. The NiCo2 O4 /NiSx, NiCo2 O4 /NiOx, and NiCo2 O4 /NiMox Oy core/shell electrodes present larger specific capacitance (CF ) but an unexpected smaller CF value is obtained for the NiCo2 O4 /MnOx core/shell electrode as compared with that for the single NiCo2 O4 nanosheet electrode, suggesting the depositing of the shell to enhance the surface area for conducting more Faradic reactions is not always helpful on improving the electrocapacitive performance of the electrode. The highest CF value of 6.12 F cm −2 is obtained for the NiCo2 O4 /NiSx electrode evaluated by using the galvanic charge/discharge curves at the current density of 1 mA cm −2, due to the superior intrinsic property of NiSx other than its high surface area of the sheets-on-sheets morphology since the structure variation is almost excluded in the work. The asymmetric supercapacitor (ASC) based on the NiCo2 O4 /NiSx positive electrode is also made with the CF value of 28.6 F g −1 based on the whole mass of the ASC at the current density of 0.5 A g −1 as well as the maximum energy density of 12.83 Wh kg −1 at a power density of 80 W kg −1 .